Representação social do corpo no desenho de escolares - Correia, Fátima Suely Barbosa da Silva (2011)
The questions of that relate to the study of child’s drawing constitute an empiricaltheoretical land, which the diversity of research has numerous and polysemic analysis in various fields of knowledge. From this aspect, it is made important to add to this discussion the analysis of this language visual-graphically on the perspective of human figure drawing, thematic of the most used by children to experiment, to develop and to build his visual and graphic expression. In this perspective, an analysis shows up, in this dissertation, about the drawing of the human figure and social representations that are unveiled from these grafismos produced by schoolboys, considering, over there to the elements that surround the design, other aspects that belong to the latent content of these graphic representations. For so much, this study enrolled in the contours of the line paradigmática of qualiquantitative research pointing to the delineation of the method of analysis of content and the results confirmed the initial hypothesis of which the children transcribe in their drawings of human figure underlying stereotypes and ideologies. On the other side, this investigation revealed that the drawings of the human figure of schoolboys also present aspects idiossincráticos what show up, in these symbolic constructions, a subject that receives and at the same time makes culture, with a look that him is peculiar and particular.